2009
DOI: 10.1016/j.jiph.2009.03.001
|View full text |Cite
|
Sign up to set email alerts
|

A survey of traditional Iranian food products for contamination with toxigenic Clostridium botulinum

Abstract: This study aimed to determine the rate of Clostridium botulinum contamination in some traditional Iranian food products (cheese, kashk and salted fish) and evaluate the efficacy of the mouse bioassay method in detection of C. botulinum toxins in these foods. A total of 131 samples (57 cheese, 11 kashk and 63 salted fish) were collected and examined to determine the rate of contamination by C. botulinum. Standard monovalent anti-toxins were used to determine the types of toxin. C. botulinum bacteria were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…For destruction of background microflora, 25 mL kashk samples were autoclaved insterile flasks prior to experimentation. Three different bacterial strains and one fungal strain were used for this study due to their previously reported presence in kashk (4,17). Escherichia coli O157: H7 (B0273), Bacillus cereus (ATCC 12480), Staphylococcus aureus (ATCC 25923), and Aspergillus fumigatus (ATCC 28216) were obtained from the Department of Food Science and Biotechnology, Kangwon National University, Korea.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For destruction of background microflora, 25 mL kashk samples were autoclaved insterile flasks prior to experimentation. Three different bacterial strains and one fungal strain were used for this study due to their previously reported presence in kashk (4,17). Escherichia coli O157: H7 (B0273), Bacillus cereus (ATCC 12480), Staphylococcus aureus (ATCC 25923), and Aspergillus fumigatus (ATCC 28216) were obtained from the Department of Food Science and Biotechnology, Kangwon National University, Korea.…”
Section: Methodsmentioning
confidence: 99%
“…Kashk is a low-fat dried yogurt lacking cereal additives produced in Iran that is used in or with many Iranian foods (4). It is produced both traditionally and industrially in both liquid and dried forms (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial growth is inhibited by refrigeration below 4 °C, heating above 121 °C, acidity (pH <4.5) or high water activity [2]. On the other hand, toxin production may occur in special conditions that include an anaerobic milieu, low-acidity (pH of >4.6), low-salt and sugar contents, no preservatives, and a proper temperature (4 °C-120 °C) [2,8,9]. Toxin is destroyed by heating to 85 °C for at least 5 min while spores are inactivated by pressure heating to 121 °C for at least 20 min [10].…”
Section: Introductionmentioning
confidence: 99%
“…The most common bacteria involved in food contamination are Salmonella spp., Campylobacter spp., Listeria monocytogenes, Escherichia coli, Staphylococcus aureus, Clostridium botulinum, Clostridium perfrigens, and Bacillus cereus [4][5][6][7].…”
Section: Bacterial Contaminationmentioning
confidence: 99%